The financial and performance cost of injuries to teams in Australian professional soccer. Issue 5 (May 2021) - Lu, Donna; McCall, Alan; Jones, Mark; Steinweg, Jeff; Gelis, Les; Fransen, Job; Duffield, Rob
Abstract: Objectives: To determine the relationship between injury incidence, player-salary cost and team performance in the professional Australian soccer league. Design: Prospective observational cohort study. Methods: Injury incidence, player-salary cost and team performance data were collected from the 10-club A-League competition (n = 27 matches/season) over 6 seasons from 2012/13. Player-salary cost of injury was calculated from the salary cap, injury-induced missed matches and player exposure, and trends were reported from Poisson regressions. Team performance was determined from ranking, points, goals (scored, conceded and difference) and match outcome (win, loss or draw) per season and analysed via a mixed-effects Poisson models to estimate association with injury. Results: Nine-hundred-and-sixteen injuries resulted in 3148 missed matches. Injury incidence remained stable apart from a decrease in 2015/16 (p = 0.01). Missed matches were significantly higher in season 2013/14 (55.1 [50.7–59.9]; p < 0.01) and 2014/15 (71.4 [66.4–76.8]; p < 0.001) compared to 2012/13, without differences between other seasons. Player-salary cost ranged between AUD$187, 990–AUD$332, 680/team, peaking in 2014/15 (p < 0.01). Multi-collinearity was detected for team performance variables except for matches lost. Teams who finished the season with greater positive goal differences were associated with 1% less injuries (p = 0.003). Similarly, more missed matches were associated with 1% less league points and losses (p < 0.001). Conclusions: Player-salary costs remained stable, concomitant with stable injury rates and missed matches. Despite injury being associated with goals difference, points and match losses; the magnitude of these relationships are small and team performance is more complex than injury occurrence alone. Injury prevention remains necessary for reducing injury-induced player-salary costs; however, additional services are required to improve team performance.